1998
DOI: 10.1046/j.1365-2036.1998.00365.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between fundic endocrine cells and gastric acid secretion in hypersecretory duodenal ulcer diseases

Abstract: The study provides evidence, for the first time, that quantitative alterations in the fundic endocrine cells are not involved in acid hypersecretion of patients with hypersecretory states, and that eradication of H. pylori does not restore normal acid secretion values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In this paper we demonstrated that H. pylori cure does not significantly affect gastric acid hypersecretion in hypersecretory duodenal ulcer patients. This finding is not in accord with those of other authors, but confirms our previous reports on smaller series 14 , . 26 27 –28 However, in this study, gastric acid hypersecretion in the absence of H. pylori infection, does not seem to be related to duodenal ulcer relapse, or to the occurrence of bleeding episodes.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In this paper we demonstrated that H. pylori cure does not significantly affect gastric acid hypersecretion in hypersecretory duodenal ulcer patients. This finding is not in accord with those of other authors, but confirms our previous reports on smaller series 14 , . 26 27 –28 However, in this study, gastric acid hypersecretion in the absence of H. pylori infection, does not seem to be related to duodenal ulcer relapse, or to the occurrence of bleeding episodes.…”
Section: Discussionsupporting
confidence: 68%
“…Some of the patients were included in other study protocols 9 , . 14 In detail, we diagnosed seven Zollinger–Ellison Syndrome patients, 14 hypersecretory duodenal ulcer disease patients and 78 duodenal ulcer patients with acid secretion in the normal range (Table 1) As reported before, we defined patients to be affected by hypersecretory duodenal ulcer when both basal and pentagastrin‐stimulated acid output were above the normal range (10 meq/h for basal acid output, 44.5 meq/h for pentagastrin acid output), with normal gastrin values 14 . Zollinger–Ellison Syndrome diagnosis was established by demonstration of repeated basal plasma hypergastrinaemia, basal acid hypersecretion and positive secretin test, as previously described 15 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also suggest the ECL mass can also have an important effect on MAO [22]. A recent study suggests that the BAO is positively correlated with the ECL-cell density in hypersecretory patients in various gastric acid hypersecretory states [78]. Since the MAO is correlated with parietal cell mass and possibly ECL cell mass and the BAO correlated with ECL-cell density, a possible explanation for the persisting hypersecretion is that contrary to what the short term studies show, after prolonged hypergastrinemia of several years duration, these ECL and/or parietal cell changes may not be completely reversible.…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori has been variously reported to cause disparate changes in gastrin and acid secretion—augmentation in some studies 3 , 7 , 8 and suppression in others 11 , 12 , 24–26 , 37 —and to change the sensitivity to stimulants such as gastrin 38 or bombesin, 7 which acts via gastrin to stimulate acid secretion in humans 39 . However, in a direct study of underlying uninhibited secretion before and 1 year after H. pylori eradication, Annibale et al 13 . found no change in elevated basal or stimulated acid outputs from pre‐treatment values in non‐ZE hypersecretors.…”
Section: Discussionmentioning
confidence: 99%